Does reclaimed water induce morphological changes in midguts of honeybees (Apis mellifera syriaca)? (Veterinary Science Development, 2014)
The purpose of this study was to assess the death rate and morphological changes in the midgut of honey worker bees when reclaimed water was the only source of drinking compared with the case when fresh water was the normal source of drinking. Two feeding solutions were implemented: fresh water sugar solution and reclaimed water sugar solution for eight consecutive days. The cages were inspected daily for any deaths of the honeybees. At the end of the experiments, midguts were removed; processed and pathological changes of the midguts were reported. The usage of reclaimed water as a drinking water had negative impacts on the average deaths of the honeybee colonies as well as the morphology of their midguts. To the best of our knowledge, no such studies have been conducted before and this is the first study that addresses the usage of reclaimed water as a sole source drinking water for honeybee colonies.